Evaluation Of Liver Enzymes (ALP, ALT, AST and GGT) in Preeclamptic Pregnant Women in the Third Trimester Of Pregnancy - Edebiri O.E; Adewole A.S; Akpe C. I; Ehigiamusoe E. A; Ikuenobe V. E; Ohiwerei W.O; Orunta E.D (Lembaga Pengembangan Kinerja Dosen, 2025)
Alkaline Phosphatase (ALP), Alanine Transaminase (ALT), Aspartate Transaminase (AST), and Gamma-Glutamyl Transferase (GGT) are liver enzymes commonly associated with liver dysfunction, and increased or decreased levels of these enzymes may be implicated in the pathophysiology of preeclampsia. This study aims to evaluate the levels of liver enzymes (ALP, ALT, AST, and GGT) in preeclamptic pregnant women in the third trimester of pregnancy. By analyzing these enzymes, the research seeks to identify potential early indicators of preeclampsia. Forty (40) consenting pregnant women were recruited from St. Philomina Catholic Hospital, Edo State, Nigeria. Blood samples were spun in a bucket centrifuge at 2500 RPM (rounds per minute) for 10 minutes, after which plasma was collected and stored frozen in plain sample bottles to be analyzed for liver enzymes (ALP, ALT, AST, and GGT) levels using the spectrophotometric method. Data obtained from the study were analyzed using Graph Pad Prism 9. Results were expressed as mean ± SEM, and a P-value of ≤ 0.05 was considered statistically significant. The present study showed a statistically significant increase in ALP, and a statistically significant decrease in liver enzymes such as ALT and AST were observed in preeclamptic women compared to normotensive pregnant women, indicating various underlying pathophysiological processes such as liver dysfunction.